2021
DOI: 10.1021/acs.jpcb.1c05609
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilicity of Intricate Layered Graphene/g-C3N4 Nanosheets

Abstract: The hybrid heterostructure of the tri-s-triazine form of graphitic carbon nitride (g-C 3 N 4 ), a stable two-dimensional material, results from intricate layer formation with graphene. In this material, g-C 3 N 4 , an amphiphilic material, stabilizes Pickering emulsions as an emulsifier and can effectively disperse graphene. Due to the various technological applications of the hybrid nanosheets in an aqueous environment, it is essential to study the interaction of water molecules with graphene and g-C 3 N 4 (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 92 publications
1
5
0
Order By: Relevance
“…However, the significant loss in tetrahedrality in the interfacial layer of h-BN compared to the bulk does not tone with the loss of HB donor/acceptor count. In our previous studies, 45,52 we found that the TOP and per water HB count follow the same trend. However, they do not complement each other quantitatively.…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…However, the significant loss in tetrahedrality in the interfacial layer of h-BN compared to the bulk does not tone with the loss of HB donor/acceptor count. In our previous studies, 45,52 we found that the TOP and per water HB count follow the same trend. However, they do not complement each other quantitatively.…”
Section: Introductionsupporting
confidence: 62%
“…The partial charge values used for B and N atoms are +0.37/–0.37 . For g–C 3 N 4 –water interactions, we used the previously reported parameters, including the charge variation over g-C 3 N 4 . As the bilayer was simulated beforehand, with both the parallel sheets flexible, during the entire simulation with water molecules, both the layers of h-BN and g-C 3 N 4 were kept static, and the water molecules were arranged according to the instantaneous surface.…”
Section: Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations